Enhancing Foreign-Language Creativity: A Didactic Approach through Audio Description - Ogea Pozo, María del Mar; Ruiz Espejel, Beatriz (Complutense Journal of English Studies, 2024)
This paper appraises the potential benefits of didactic audiovisual translation, aiming to enhance learners’ acquisition and proficiency of English as an L2 through audio description techniques. These action-oriented tasks involve two phases: a systematic analysis of the source audiovisual text, and a cross-modal rendering of meaning into a suitable target text, in which learners are required not only to be faithful to the visual information, but also be fluent in the target language to produce an accurate and effective audio description. In this regard, a qualitative study has been conducted to assess the learning outcomes of participants in a course on didactic audio description, particularly in terms of speaking skills and creativity. For this purpose, a corpus has been compiled from the transcripts of their audio descriptions in English. This corpus allows for the exploration of how learners describe orally visual aspects related to actions, physical appearance, and emotions, as well as their competence in expressiveness, utterance, and other communicative skills. The learning outcomes related to speaking skills and creativity are promising, and advocate for a more comprehensive and integrated pedagogical approach to Audiovisual Translation teaching in the Translation and Interpreting and the Foreign Language Education curricula.